PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN PENDEKATAN THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 005 DESA BINUANG - Robbiati, Robbiati; Saragih, Sehatta; Syofni, Syofni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study aims to improve students' mathematics learning outcomes by implementing Cooperative Learning Think Pair Share (TPS) in class V SD Negeri 005 Desa Binuang. In the first semester of academic year 2012/2013. This study uses classroom action research. the subject studied were student of class V SD Negeri 005 Desa Binuang, with academic and social heterogeneous. Implementation phase of this study consisted of planning, action, observation, reflection. conducted in two cycles, six meetings and two quizzes. The activity student and teachers learning outcomes data were gained by collecting activity data by using observation sheets, and test. Analysis of the data used descriptive analysis that describes the activities of teachers and students, analysis of the results of learning mathematics. The conclusions of this study indicate that Cooperative Learning Think Pair Share can improve mathematic learning outcomes.Keywords: Cooperative Learning Model, TPS, Learning Outcomes